The origins and professionalization of cognitive psychotherapy in Argentina - Korman, Guido Pablo (2015)
The growing popularity of cognitive-behavioral therapy (CBT) has helped reshape the mental health scene in the city of Buenos Aires, historically the stronghold of psychoanalysis. In the early 1980s, CBT was infrequently used and sometimes overtly resisted in the field of mental health. Almost three decades later, the impact of CBT has increased dramatically in Argentina, not only in private practice, but also in the health system and in everyday life. This paper aims to describe the process by which Argentine psychotherapists first adopted this new theoretical framework.